Algoritmi za reinverzijo bazne matrike v linearnem programu - Barle, Janez (Informatica (Ljubljana), 1985)
We describe some of the algorithms for matrix reinversion which can be appliedin the procedures for solving the linear programming problem. They use a specific presentation of the inverse matrix and two-phase computation process. Special attention is paid to those problems associated with the computer processing of these algorithms.
Keywords: algoritmi za invertiranje matrike; analitična faza inverzije; dvofazni postopek inverzije; linear algebra; linear programming; linearna algebra; linearno programiranje; matematika; mathematics; matrix reinversion; numerična faza inverzije; specifična forma inverzne matrike